Anomalous behaviour of electric resistivity in Co-Si-B based metallic glasses - Babich, M.G.; Nosenko, V.K.; Semen'ko, M.P.; Yeremenko, G.V.; Zakharenko, M.I. (Functional Materials, 2005)
Temperature dependences of electric resistivity have been investigated in 300-950 К temperature range for Со₆₅.₅Ме₆.₅(Si,B)₂₈ metallic glasses (Ме = Fе, Сr). Several characteristic temperature intervals have been distinguished in ρ(Т) dependences. The minimum of resistivity has been shown to be directly related with the presence of chromium and to be of magnetic nature.